?-STATISTICAL CONVERGENCE OF ORDER ? - Colak, R.; Bektas, C. A. (Springer, 2011)
In this paper, we introduce the concept of lambda-statistical convergence of order alpha. Also some relations between the lambda-statistical convergence of order alpha and strong (V, lambda)-summability of order alpha are given.
Keywords: sequences; statistical convergence; Cesaro summability